Terrorism and Homeland Security : an Introduction with Applications. - Purpura, Philip (Butterworth-Heinemann Homeland Security., 2006)
Provides a comprehensive introduction to the problem of terrorism and to its proposed solution in the U.S., namely, Homeland Security, its missions, goals, and strategies.